2017
DOI: 10.1007/s42114-017-0014-1
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic negative permittivity with dielectric resonance in random Fe3O4@graphene-phenolic resin composites

Abstract: Magnetic Fe 3 O 4 @graphene-phenolic resin (FGR-PR) composites with negative permittivity were prepared by chemical coprecipitation and pressing method. Alternating current conductivity, permittivity, and permeability of the FGR-PR composites were investigated. An obvious percolation phenomenon was observed with the increase of FGR content from 84 to 91 vol%. Two types of negative permittivity attributed to the Lorentz and the Drude model, respectively, w e r e o b s e r v e d i n t h e c o m p o s i t e s . D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(26 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…37 Similar behavior of dielectric loss was also observed by Wu et al and was shown to be dependent on the dopant concentration in the solution. 47 This type of peaking behavior is observed when the jumping frequency of the Fe 2þ and Fe 3þ ions is exactly equal to the frequency of the applied field. 48 In the present case, the abrupt increase in the dielectric loss can be related to similar type of concentration-dependent behavior.…”
Section: Dielectric Constant and Dielectric Loss Studiesmentioning
confidence: 97%
“…37 Similar behavior of dielectric loss was also observed by Wu et al and was shown to be dependent on the dopant concentration in the solution. 47 This type of peaking behavior is observed when the jumping frequency of the Fe 2þ and Fe 3þ ions is exactly equal to the frequency of the applied field. 48 In the present case, the abrupt increase in the dielectric loss can be related to similar type of concentration-dependent behavior.…”
Section: Dielectric Constant and Dielectric Loss Studiesmentioning
confidence: 97%
“…21 Recently, iron-bearing materials have been applied to various elds such as drug delivery, sensors, electromagnetic interference shielding, and adsorbents for environmental remediation. [22][23][24] In the environmental eld, iron-bearing materials such as magnetite, 25,26 iron suldes, 27,28 goethite, 29 and zerovalent iron 30 can remediate Cr(VI). It has also been reported that fabric-and cellulose-derived magnetic carbon-iron nanomaterials possess high efficiency for Cr(VI) removal, 31,32 where Cr(VI) is reduced to Cr(III) by the reductive intermediates generated from ZVI such as Fe(II).…”
Section: àmentioning
confidence: 99%
“…38 composites. 63 The transition of dielectric constant from positive to negative (75 to -75) was observed in the FGR-PR composites when the FGR content reached 91 vol%. According to the Lorentz model, the negative permittivity appeared when the frequency of applied electromagnetic field exceeded the resonance frequency, and the resonance frequency for FGR91 was about 460 MHz.…”
Section: Metacomposites With Gr As Fillersmentioning
confidence: 94%